新超伝導重力計（OSG#058）の設置 - 池田, 博; 青山, 雄一; 早河, 秀章; 土井, 浩一郎; 津和, 佑子; 菅原, 安宏; 澁谷, 和雄; Hiroshi, IKEDA; Yuichi, AOYAMA; Hideaki, HYAKAWA; Koichiro, DOI; Ikuko, TSUWA; et al. (2010)
第30回極域地学シンポジウム「極域から探る固体地球ダイナミクス」 ポスター発表 conference object